Impacts of people at-risk of either cow milk allergies or lactose intolerance on their daily calcium intake and bone mineral density - Kongpharm, Kornkanok; Nakklay, Parinda; Kongtong, Chunhakan; Tanapumchai, Pichaya; Prapkree, Lukkamol; Rueangsri, Narisa; Singhato, Alongkote (Frontiers in Nutrition, 2024)
Background: People who are at-risk of either cow milk allergies or lactose intolerance may need to avoid consuming milk and milk products which are well known as abundant sources of calcium (Ca). This could affect bone health by limiting Ca intake. Nowadays, there is limited knowledge on the impact of people at -risk of cow milk allergies on their daily Ca intake and bone mineral density (BMD). This study aimed to investigate the differences between the amount of Ca intake and BMD values among at risk of cow milk allergies and non-risk people.Methods: Eighty participants were recruited and further conducted the quota sampled into 2 groups; at-risk cow milk allergies (AR) group (n=40) and normal (NOR) group using the cow milk allergies and lactose intolerance screening questionnaire. All participants completed the anthropometric assessment, body composition analyses, 3-day dietary record, and bone mass density (wrist and ankle bone) measurement using the dual x-ray absorptiometry (DEXA) technique to compare the differences of variables between 2 groups.Results: Participants in the AR group presented a significantly lower amount of Ca intake (317 mg/day) than the NOR group (623 mg/day) (p<0.05). The bone mineral density (BMD) parameters found that there were significantly higher T-scores and BMD values of wrist (T-score = -0.27 and BMD = 0.57 g/cm2) and ankle (T-score = -0.01 and BMD = 0.59 g/cm2) bone when compared with the AR group (T-score = -1.96 and BMD = 0.48 g/cm2 for wrist, and T-score = -1.18 and BMD = 0.47 g/cm2 for ankle) (p<0.05). In addition, results indicatedthe significantly positive correlations between the amount of Ca intake and the T-scores and BMD values of both wrist and ankle bone among participants (p<0.05).In this responding sample, participants at-risk of cow milk allergies had a significantly negative impact on the amount of Ca intake and BMD values.Professionals in nutrition and dietetics should provide nutrition education and strategies that enhance the Ca intake among this population to help them meet daily Ca intake recommendation leading to better bone health.